Formation of Managers’ Competencies in The Field of Project Portfolio Management of The Enterprise - H. H. Kuchmezov; S. I. Neizvestny (Открытое образование (Москва))
The purpose of this study is to analyze existing approaches to managing a portfolio of projects and programs, their further development and generalization, the creation of systems focused on creating the competence of specialists in the field of managing enterprise project portfolios. The substantiation and main reasons for the need to form the competencies of specialists in project portfolio management from the point of view of the effectiveness of project activities and business of the enterprise are discussed.In modern conditions, the functioning of any company is determined by a number of global trends - a change in business formats under the influence of digitalization, networkization of the economy, and changes in the structure of transaction costs, optimization of project portfolio management. This, in turn, entails a change in the requirements for the competencies of managers in managing enterprise project portfolios. The higher education system currently does not form the necessary set of competencies for university graduates, who should be functionally involved in managing a portfolio of projects and programs. Project portfolio management competencies are erroneously replaced by individual project management competencies, while almost all modern enterprises have a project portfolio. This is one of the reasons why the managers of the enterprise, when hiring yesterday’s university graduates, formulate an introductory requirement for them: - “Forget everything you were taught at the university”.Materials and methods. The study was conducted from 2019 to 2021 at the Financial University under the Government of the Russian Federation among 4th year students of the direction of study “Business Informatics”, studying in the profile “IT Management in Business”. The methodological basis of the study was a set of theories of innovation management, portfolio and project management. The typology of project portfolios is represented by the core competencies required by managers in managing project and program portfolios. An analysis of the existing education system shows that even after a master’s degree it is not capable of providing businesses with a professionally trained manager of large projects, not to mention a bachelor’s degree. Some limitations in the use of well-known portfolio management competencies due to their inconsistency with current business realities are noted. The main research method was the analysis of modern requirements for the functionality of the organization’s project portfolio management system.Results. It was revealed that the main requirements of modern business in specialists with competencies in managing a portfolio of projects and programs are significantly ahead of the existing competencies of university graduates. The main necessary competencies of project portfolio managers are determined. The gap in business requirements and existing competencies of university graduates in this direction of management is shown. The results obtained in the study can be used in the formation of competencies in the management of a portfolio of projects that the business presents to the education system.Conclusion. Project and program portfolio management is a significant factor in the development of an enterprise’s business. Business conditions are now such that enterprises simultaneously implement several projects and programs, these projects and programs are forced to be combined into portfolios. In portfolios, projects compete for the limited resources of the enterprise, and in the absence of systemic management of the project portfolio, lack of coordination between them, managerial chaos may arise that harm both individual projects and the entire business of the enterprise. Thus, combining individual projects into programs, and programs into portfolios, significantly increases the efficiency of project activities and the business of the enterprise as a whole.Using the example of Sberbank, the article compares the list of competencies required by the business functionality in the field of managing portfolios of projects and programs with the assessment of the competence of graduates in the direction of business informatics. The results obtained in the study can be used in the transformation of personnel training systems, in practical activities for managing portfolios of projects and programs of organizations of any type.